Designing Guidebook for Writing Arabic Calligraphy Rules for Beginners - Pratama, Adithya (Assyfa Journal of Multidisciplinary Education, 2025)
Arabic calligraphy, renowned for its artistic and spiritual significance in Arab culture, presents a unique challenge for beginners due to its intricate rules and techniques. This research aims to create an effective guidebook to aid novices in comprehending and mastering the essentials of Arabic calligraphy. Employing a qualitative approach with a development research method, the study begins with a thorough literature review to gather insights into the foundational principles of Arabic calligraphy and the requirements of learners. The guidebook's design phase incorporates structured content, step-by-step learning instructions, practical exercises, and user-friendly guidelines. Tested with a group of beginners over a defined period, data was collected through observations, interviews, and assessments by both learners and calligraphy experts. Findings indicate that the guidebook significantly enhances beginners' comprehension and skills in Arabic calligraphy, offering practical steps and accessible guidance. This research contributes to the development of instructional materials for Arabic calligraphy, acting as a valuable reference for calligraphers and art educators in creating effective learning tools. It underscores the necessity for structured guidance for aspiring calligraphers. The validity test results reveal a 93.6% approval rating from media experts and an 83.1% feasibility score from beginners, confirming the guidebook's efficacy.